Preliminary phytochemical screening, FT-IR, and HPTLC analysis, and antioxidant, antimicrobial activities of methanolic extracts of Dalbergia sisso leaves - Chaddha, Varun; Gupta, Reena (Creative Pharma Assent, 2025)
Background: Dalbergia sissoo is a well-known plant known as Shisham. It has medicinal importance, including analgesic, antipyretic, and antiemetic properties. Therefore, the primary objective of this research is to investigate the bioactive constituents in the methanolic leaf extract of Dalbergia sisso by characterizing it using FT-IR and HPTLC techniques, and to determine its antioxidant and antimicrobial activities. Methodology: A Soxhlet apparatus was used for the extraction process. 150 g of Dalbergia sisso powdered leaves was extracted using a Soxhlet apparatus for 30 hours, utilizing methanol as a solvent. The solvent was vaporized and concentrated to produce a dry residue once the extraction was finished. The yield percentages for the methanolic extract were 4.8% respectively. Result and Discussion: FT-IR spectroscopy showed different peak values for functional compounds in the methanolic extract. The FTIR spectrum of the methanolic leaf extract shows the interpretation of the chemical bonds in the methanolic leaf extract. HPTLC studies revealed that the active compound lupeol is present in the methanolic extract. Conclusion: It has been concluded that the methanolic extract of Dalbergia sisso leaves contains lupeol and quercetin bioactive compounds. The methanolic extract of Dalbergia sisso leaves was found to have antioxidant and antimicrobial effects. The HPTLC technique found lupeol, which may possess antioxidant and antimicrobial activities. The FT-IR spectrum revealed the presence of hydroxyl, hydrocarbon, aldehyde, allene, and secondary alcohol groups in the methanolic extract, consistent with the presence of quercetin. The methanolic leaf extracts show the presence of saponin, alkaloids, flavonoids, anthraquinone glycosides, and tannins.